(untitled) (Physical Education, Health and Social Sciences, 2025)
Raw vegetables form a fundamental constituent of the human diet due to their nutrient contents but are a major public health risk when consumed without washing and cooking. In the developing countries like Pakistan, the spread of intestinal parasites through vegetables is facilitated by open-air marketing, contaminated irrigation water, and inadequate hygiene standards. The purpose of this study was to determine the types and prevalence of parasitic infestations in raw vegetables that are often consumed in District Swat, Khyber Pakhtunkhwa, Pakistan. Between May and September, 100 raw vegetable samples (20 of each of tomato, cucumber, lettuce, carrot, and mint) were collected at random from neighbourhood stores, food stands, and street sellers. After being cleaned and immersed in 0.85% saline solution, each sample was filtered, centrifuged for 10 minutes at 5000 rpm, and examined under a microscope at 10× & 40× magnifications.The parasites were identified on the basis of morphology using standard keys of parasitology and WHO guidelines. Twenty-five (25%) of 100 samples harbored one or more parasites. The maximum rate of contamination was in carrot (50%), followed by mint (35%) and lettuce (25%). Cucumber and tomato were least contaminated with 10% and 5%, respectively. Ascaris lumbricoides, Taenia species, Brugia malayi, Strongyloides stercoralis, Toxocara eggs, and hookworms were among the parasites identified. The results showed that raw vegetables in the research area provide a significant risk of intestinal parasite transmission. Improving food handling procedures, raising public awareness, and using appropriate washing methods are all extensively needed to significantly decrease the health hazards connected to contaminated produce.